PENGARUH PERSEPSI TENTANG CORPORATE SOCIAL RESPONSIBILITY TERHADAP REPUTASI PERUSAHAAN YANG DIMEDIASI OLEH CITRA MEREK - Sugiarti, Ni Wayan (E-Jurnal Manajemen, 2015)
This study aimed to determine the effect of perception of Corporate Social Responsibility (CSR) to the reputation of the company which is mediated by the brand image. This research was conducted in Gianyar. The samples are 65 respondents. Analytical technique used is path analysis and Sobel test. Based on the analysis of data known to have a positive impact of CSR on brand image; there is a positive effect of CSR on the company's reputation; there is the influence of brand image on the company's reputation. Based on the analysis, it can be submitted suggestions that Toyota still do CSR because it can enhance the brand image and reputation of Toyota.
Keywords: CSR, Brand Image, Corporate Reputation